Hand-arm vibration and the risk of vascular and neurological diseases-A systematic review and meta-analysis. - Tohr Nilsson; Jens Wahlström; Lage Burström (PLoS ONE)
Background Increased occurrence of Raynaud's phenomenon, neurosensory injury and carpal tunnel syndrome has been reported for more than 100 years in association with work with vibrating machines. The current risk prediction modelling (ISO-5349) for "Raynaud's phenomenon" is based on a few studies published 70 to 40 years ago. There are no corresponding risk prediction models for neurosensory injury or carpal tunnel syndrome, nor any systematic reviews comprising a statistical synthesis (meta-analysis) of the evidence. Objectives Our aim was to provide a systematic review of the literature on the association between Raynaud's phenomenon, neurosensory injuries and carpal tunnel syndrome and hand-arm vibration (HAV) exposure. Moreover the aim was to estimate the magnitude of such an association using meta-analysis. Methods This systematic review covers the scientific literature up to January 2016. The databases used for the literature search were PubMed and Science Direct. We found a total of 4,335 abstracts, which were read and whose validity was assessed according to pre-established criteria. 294 articles were examined in their entirety to determine whether each article met the inclusion criteria. The possible risk of bias was assessed for each article. 52 articles finally met the pre-established criteria for inclusion in the systematic review. Results The results show that workers who are exposed to HAV have an increased risk of vascular and neurological diseases compared to non-vibration exposed groups. The crude estimate of the risk increase is approximately 4-5 fold. The estimated effect size (odds ratio) is 6.9 for the studies of Raynaud's phenomenon when including only the studies judged to have a low risk of bias. The corresponding risk of neurosensory injury is 7.4 and the equivalent of carpal tunnel syndrome is 2.9. Conclusion At equal exposures, neurosensory injury occurs with a 3-time factor shorter latency than Raynaud's phenomenon. Which is why preventive measures should address this vibration health hazard with greater attention.